2010
DOI: 10.1038/hr.2010.68
|View full text |Cite
|
Sign up to set email alerts
|

Circadian clock and vascular disease

Abstract: Cardiovascular functions, including blood pressure and vascular functions, show diurnal oscillation. Circadian variations have been clearly shown in the occurrence of cardiovascular events such as acute myocardial infarction. Circadian rhythm strongly influences human biology and pathology. The identification and characterization of mammalian clock genes revealed that they are expressed almost everywhere throughout the body in a circadian manner. In contrast to the central clock in the suprachiasmatic nucleus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 89 publications
0
48
0
4
Order By: Relevance
“…B lood pressure follows a circadian rhythm which is coordinated by circadian Clock genes [1] and the diurnal rhythmicity of nitric oxide [2]. This circadian rhythm is lost in hypertension [1,2], and in insulin-resistant states such as obesity [3] and diabetes [4,5], and is associated with blunted endothelium vasodilation and adverse cardiovascular events [6].…”
Section: Introductionmentioning
confidence: 99%
“…B lood pressure follows a circadian rhythm which is coordinated by circadian Clock genes [1] and the diurnal rhythmicity of nitric oxide [2]. This circadian rhythm is lost in hypertension [1,2], and in insulin-resistant states such as obesity [3] and diabetes [4,5], and is associated with blunted endothelium vasodilation and adverse cardiovascular events [6].…”
Section: Introductionmentioning
confidence: 99%
“…1). 82,104,113 For example, Millar-Craig et al 82 have shown that BP is lowest at around 3 AM and increases gradually during the early morning hours before waking, reaching a peak at midmorning. The BP rise that begins before waking was not associated with physical activity.…”
Section: Circadian Blood Pressure Variationmentioning
confidence: 99%
“…A large epidemiological studies have found that circadian rhythm upset is associated with breast cancer for lighting effects. Women on the night shift and working in shifts have increasingly risk of developing breast cancer [8,12] . Elisabeth Filipski's research found the circadian clock disorders can speed up the development of liver cancer [13] .…”
Section: Discussionmentioning
confidence: 99%